Teaching through Stories. Renewing the Scottish Storyline Approach in Teacher Education - Kristine Høeg Karlsen (Waxmann Verlag, 2020)
This book aims to meet the demands on teaching and learning in the twenty-first century, and in specific, how teacher education may transform pedagogical approaches and didactic methods to support future teachers in enhancing needful skills. In particular, it focuses on the pedagogical approach of Storyline, and how a Storyline can be applied in teacher education. It argues that teacher education benefits from the potency of various disciplines while applying an interdisciplinary methodology. Storyline is a problem-based, cross-curricular approach, based on learning through an evolving narrative, created in collaboration between teacher and students. It includes a variety of didactic tools, and inclusiveness towards different learners. Using Storyline in teacher education arranges for teacher educators to integrate alternative structures, that enable interdisciplinary cooperation and topic-based teaching. The authors have incorporated Storyline in many different ways, which contextualizes throughout the book. The book provides an overview of Storyline and introduces improved and new theoretical perspectives on this approach, including many practical examples.